"Isofacet" Anatase TiO2 Microcages: Topotactic Synthesis and Ultrastable Li‐Ion Storage. Issue 14 (23rd July 2015) - Wu, Qili; Yang, Xianfeng; Zhou, Wuzong; Gao, Qiong; Lu, Fengqi; Zhuang, Jianle; Xu, Xianfang; Wu, Mingmei; Fan, Hong Jin
<x xml:space="preserve">Abstract</x> A new type of hierarchical anatase TiO2 microcage is obtained via an in situ topotactic transformation from prefabricated CaTiO3 microcages. The TiO2 microcages are composed of 3D perpendicular nanocrystals with six equivalent side faces that are dominated by anatase 001A facets. As an anode material these unique anatase TiO2 microcages exhibit high‐rate lithium ion storage and long‐cycling stability.